Pectolinarigenin Induces Antioxidant Enzymes through Nrf2/ARE Pathway in HepG2 Cells - Mariko Shiraiwa; Tomoya Kitakaze; Yoko Yamashita; Yuichi Ukawa; Katsuyuki Mukai; Hitoshi Ashida (MDPI AG, 2022)
Pectolinarigenin (PG) and its glycoside pectolinarin (PN) were reported to have various health beneficial functions such as anti-inflammatory and anti-carcinogenic activities. It has also been reported that PG and PN have radical scavenging ability as direct antioxidant activity. However, the indirect antioxidant activity of PG and PN by inducing antioxidant enzymes in hepatocytes is not fully understood yet. In this study, we investigated whether PG and PN increase expression of antioxidant enzymes through the nuclear factor-erythroid-2-related factor 2 (Nrf2)-mediated pathway in human hepatoma HepG2 cells and the liver of male ICR mice. PG, but not PN, induced antioxidant enzymes, namely heme oxigenase-1, NAD(P)H:quinone oxidoreductase 1, and aldo-keto reductase family 1 member B10, in HepG2 cells. As for the induction mechanism of these enzymes, PG-induced nuclear accumulation of Nrf2 increased antioxidant response element (ARE)-mediated transcriptional activity and suppressed degradation of Nrf2 through modification of Kelch-like EXH-associated protein 1. Oral administration of PG also induced nuclear accumulation Nrf2 and expression of antioxidant enzymes in the liver of mice. Therefore, PG, but not PN, exhibits the indirect antioxidant activity by inducing antioxidant enzymes through the Nrf2/ARE pathway and may protect liver from oxidative stress.